Taxes and the Fisher Effect: A Clarifying Analysis - MILES, JAMES A. (Journal of Finance, 1983)
ABSTRACT Supply and demand functions for loanable funds are postulated for a no‐inflation economy and equilibrium levels of saving, investment, and the interest rate are specified. Certainty and nondepreciating assets are assumed. An exogenous inflation rate is imposed upon this same economy and new equilibrium values for these same variables are established. The analysis is performed twice. The first time, a Modigliani‐Miller [17] tax structure is assumed while the second analysis assumes a Miller‐Scholes [15] tax structure. In both cases, inflation causes the nominal rate to increase by more than the inflation rate. The analysis is repeated assuming that investments live for one period and are then written off against taxable income at historical cost. In both tax structures, the level of saving and investment is a decreasing function of the inflation rate.